Seputik Sekar Cakap: Upaya Mengedukasi Perempuan dalam Pemenuhan Gizi Balita sebagai Langkah Pencegahan Stunting - Farzana, Liana Afza; Rahmawati, Reni; Diani, Winasti Rahma (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
The women's school in Pucungroto Village uses a non-formal curriculum to establish women's ability level in knowledge and skills to minimize the level of stunting rates in Pucungroto Village. Pucungroto Village was the choice of the PPK Ormawa Himaprodi PBSI Team to carry out a women's school program which aims to empower the Pucungroto Village community for women through the Seputik Sekar program, especially in terms of health and nutrition. The development of women in Pucungroto Village uses several methods, including location surveys, identifying community needs, pioneering partnerships with various parties outside the village, developing a curriculum involving stakeholders, carrying out outreach activities, implementation, monitoring and evaluation stages. Coaching and mentoring is carried out directly and actively for the women of Pucungroto Village. Involvement of partners and agencies to support program sustainability, and evaluation using a Likert scale to assess the level of knowledge and satisfaction of targets, so as to obtain data on increasing women's understanding and skills in aspects of health and nutrition.  The hope of the Seputik Sekar Cakap program is that it will be a sustainable activity which can later be carried out with PKK mothers, partners, and students or PPK Ormawa activity activists who are able to improve and provide something new as an effort to improve the welfare of the Pucungroto Village community.